Epiphyseal Cartilage Formation Involves Differential Dynamics of Various Cellular Populations During Embryogenesis - Zhang, Yi; Annusver, Karl; Sunadome, Kazunori; Kameneva, Polina; Edwards, Steven; Lei, Guanghua; Kasper, Maria; Chagin, Andrei S.; Adameyko, Igor; Xie, Meng (Frontiers in Cell and Developmental Biology, 2020)
A joint connects two or more bones together to form a functional unit that allows different types of bending and movement. Little is known about how the opposing ends of the connected bones are developed. Here, applying various lineage tracing strategies we demonstrate that progenies of Gdf5-, Col2-, Prrx1- and Gli1-positive cells contribute to the growing epiphyseal cartilage in a spatially asymmetrical manner. In addition, we reveal that cells in the cartilaginous anlagen are likely to be the major sources for epiphyseal cartilage. Moreover, Gli1-positive cells are found to proliferate along the skeletal edges towards the surface of the epiphyseal cartilage. Finally, a switch in the mechanism of growth from cell division to cell influx likely occurs at the epiphyseal cartilage when joint cavitation has completed. Altogether, our findings reveal an asymmetrical mechanism of growth that drive the formation of epiphyseal cartilage ends, which might implicate on how the articular surface of these skeletal elements acquires their unique and sophisticated shape during embryonic development.